Existence, regularity and asymptotic behavior of solutions for a nonlocal Chafee-Infante problem via semigroup theory - Caraballo, Tomás; Carvalho, Alexandre N.; Julio, Yessica (Topological Methods in Nonlinear Analysis, 2025)
This article deals with the study of a non-local one-dimensional quasilinear problem with continuous forcing. We use a time-reparameterization to obtain a semilinear problem and study a more general equation using semigroup theory. The existence of mild solutions is established without uniquenesswith the aid of the formula of variation of constants and asking only a suitable modulus of continuity on the nonlinearity this mild solution is shown to be strong. Comparison results are also established with the aid of the formula of variation of constants and using these comparison results, global existence is obtained with the additional requirement that the nonlinearity satisfy a structural condition. The existence of pullback attractor is also established for the associated multivalued process along with the uniform bounds given by the comparison results with the additional requirement that the nonlinearity be dissipative. As much as possible the results are abstract so that they can be also applied to other models.